Parents’ Beliefs about Their Children’s Academic Ability: Implications for Educational Investments - Dizon-Ross, Rebecca (American Economic Review, 2019)
Schools worldwide distribute information to parents about their children’s academic performance. Do frictions prevent parents, particularly low-income parents, from accessing this information to make decisions? A field experiment in Malawi shows that, at baseline, parents’ beliefs about their children’s academic performance are often inaccurate. Providing parents with clear, digestible performance information causes them to update their beliefs and adjust their investments: they increase the school enrollment of their higher-performing children, decrease the enrollment of lower-performing children, and choose educational inputs that are more closely matched to their children’s academic level. Heterogeneity analysis suggests information frictions are worse among the poor. (JEL C93, D83, I21, I24, J13, O15)